DECREASE OF DISMENORE SCALE SCREENING WITH GINGER HERBAL THERAPY AND YELLOW ACID IN FEMALE STUDENT MUHAMMADIYAH VOCATIONAL SCHOOL 2 KLATEN UTARA - Kusumawati Priyono, Putri (INVOLUSI: Jurnal Ilmu Kebidanan, 2019)
Background: Dysmenorrhea is pain during menstruation until there is a result of pain that can interfere with daily activities and make women uncomfortable in the lower abdomen accompanied by cramps, nausea, dizziness, and fainting. Dysmenorrhea can be treated using therapeutic ginger and turmeric acid. Objective: To determine the decrease in the score of dysmenorrhea scale with the therapy of ginger and sour turmeric on the students of North Klaten Muhammadiyah 2 Vocational School. Research Methods: This study used a quasy experiment design with a non randomized control group pretest posttest design. The sampling technique used purposive sampling with 30 respondents. The instrument used was the Numeric Rating Scale questionnaire. The data analysis used was the Wilcoxon test. Research Results: The average decrease in the dysmenorrhea scale score in the control group was 6.25 and the trial group was 7 with the control group p-value 0.029 and the trial group 0.002 (p <0.005). Conclusion: Herbal turmeric acid therapy is more effective in reducing dysmenorrhea scale score in Klaten North Muhammadiyah 2 Vocational School 2 students compared to ginger herbal therapy.